Microsatellites as research tools : proceedings of COSPAR Colloquium on Microsatellites as Research Tools held in Tainan, Taiwan, 14-17 December 1997 /: proceedings of COSPAR Colloquium on Microsatellites as Research Tools held in Tainan, Taiwan, 14-17 December 1997. (1999) - Unknown
No abstract available